2022
DOI: 10.1155/2022/2957844
|View full text |Cite|
|
Sign up to set email alerts
|

CircKMT2E Participates in Osteoarthritis through Promotes Apoptosis of Chondrocytes Via Sponging miR-140-5p to Activate TLR4

Abstract: Objective To explore the latent pathogenesis of circRNAs in osteoarthritis (OA), as well as their function mechanism. Methods The murine chondrocytes with and without OA were involved and used for in-depth sequencing. Herein, we carried out subsequent bioinformatics analysis to disclose the expression pattern, characteristics of circRNAs based on gene ontology, and the KEGG pathway analyses. Then sequencing data were used to deduce the interaction between circRNA and mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%